HOW LISTENING TO ENGLISH PODCASTS CAN ENHANCE COMPREHENSION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the role of social media and podcasts in enhancing English language learning, especially listening skills. It emphasizes how platforms like Facebook, YouTube, and Spotify can expose learners to authentic English, help expand vocabulary, and improve pronunciation and comprehension. The article also discusses challenges such as fast-paced speech and lack of visuals, while suggesting practical solutions like using transcripts and consistent practice. It concludes that combining traditional methods with digital tools creates an effective and modern approach to language learning.